Enterprise Competitive Positioning Based on Knowledge Resources Identification - Vartanova, Olena; Bilyk, Victoriia; Budnikevich, Iryna; Kolomytseva, Olena; Vasylchenko, Lidiia (Entrepreneurship and Sustainability Issues., 2021)
Competitive advantages of modern companies are determined by a set of resources that discover the uniqueness of the company in the market and find out its competitive position. The authors conceptualized the process of determining the company’s competitive position based on the identification of knowledge resources. Competitive positioning is understood as the process of forming, maintaining and strengthening the company's competitive position based on the audit of key knowledge resources (their types, location, carriers and directions of movement), which form key areas of the company’s competence and create sustainable competitive advantages. The sequence of the enterprise competitive positioning on new resources of knowledge which reveals stages of competitive position definition is offered. The tools and methods of estimating knowledge resources in the competitive positioning of the company are formed. The matrices of the company's competitive position are constructed, which determine the competitive advantages and competitive weaknesses of the company. Criteria for interpreting the results of the company competitive positioning based on knowledge resources are proposed. They identify main company’s competitive advantages and weaknesses. In the article resources of knowledge that form company’s competitive advantages and weaknesses are defined. Competitive advantage matrices are built. Criteria for the results of company’s competitive positioning on new knowledge resources interpreting are suggested.
Keywords: competitive advantages; competitive positioning; identification; measurement; knowledge resources